Gender Specific Differences in Prevalence and Risk Factors for Gastro-Esophageal Reflux Disease - Kim, Sang Yoon; Jung, Hye-Kyung; Lim, Jiyoung; Kim, Tae Oh; Choe, A Reum; Tae, Chung Hyun; Shim, Ki-Nam; Moon, Chang Mo; Kim, Seong-Eun; Jung, Sung-Ae (Journal of Korean medical science, 2019)
Gender-related factors might play an important role in the development of reflux esophagitis (RE) and symptomatic gastro-esophageal reflux disease (GERD). We aimed to evaluate the prevalence and risk factors for RE and symptomatic GERD and determine whether gender specific differences exist. This study was conducted on a health cohort consisting of 10,158 participants who underwent comprehensive health screening. Lifestyles and gastrointestinal symptoms were investigated using a self-reported structured questionnaire. Questionnaires about menstrual status were added for the women. The prevalence of RE in men was significantly higher than that in women (10.6% vs. 2.0%, < 0.001); however, symptomatic GERD showed predominance in women (6.2% vs. 2.5%, < 0.001). Although the prevalence of RE gradually increased with the duration of menopause stratified by decade ( = 0.007), that of symptomatic GERD rapidly increased across the menopausal transit in women. Apart from common risk factors of obesity and current smoking for RE, over 70 years of age in women and hiatal hernia and hypertriglyceridemia in men were significant risk factors. In symptomatic GERD, high somatization was a common risk factor. Excessive alcohol drinking was a significant risk factor in men, but not in women. This study showed a predominance of RE in men, but a predominance of symptomatic GERD in women. In women, dynamic increase in the prevalence of GERD is closely related to the menopause conditions and its duration. There are specific risk factors for RE and symptomatic GERD according to gender differences.